2022
DOI: 10.1080/10717544.2021.2023696
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria targeting molecular transporters: synthesis, lipophilic effect, and ionic complex

Abstract: As mitochondria are potential therapeutic targeting sites for the treatment of human diseases, delivering cytotoxic drugs, antioxidants, and imaging molecules to mitochondria can provide new therapeutic opportunities. In an attempt to develop a new mitochondria-targeting vector, we synthesized sorbitol-based molecular transporters with multiple guanidines, measured their partition coefficients, compared their targeting efficiency using fluorescent images and Pearson's correlation coefficients, and studied cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…59 To overcome this, lipophilic molecules are preferred due to their membrane permeability, facilitated by hydrophobic interactions. 60…”
Section: Mitochondrial Structure and Molecule Entrymentioning
confidence: 99%
“…59 To overcome this, lipophilic molecules are preferred due to their membrane permeability, facilitated by hydrophobic interactions. 60…”
Section: Mitochondrial Structure and Molecule Entrymentioning
confidence: 99%
“…Delivering cytotoxic drugs, antioxidants, and other agents to mitochondria can be a novel strategy for treating intractable diseases. [153][154][155][156][157][158] Xu et al demonstrated perimitochondrial enzymatic peptide self-assembly to target mitochondria in liver cancer cells selectively (Figure 4B). Here, enterokinase in the mitochondria cleaved the peptide-lipid conjugates and delivered encapsulated chloramphenicol to cancer cell mitochondria to avoid inactivation, inhibiting mitochondrial protein synthesis, thereby inducing cell death and resensitizing drugresistant cells to cisplatin.…”
Section: Target Organellesmentioning
confidence: 99%
“…Several research groups have successfully achieved the in situ self‐assembly of peptide derivatives at the tumor tissue and even at cancer cell subcellular organelle levels. Delivering cytotoxic drugs, antioxidants, and other agents to mitochondria can be a novel strategy for treating intractable diseases 153–158 . Xu et al.…”
Section: Subcellular Internalization and Precise Target Nano‐drug Systemmentioning
confidence: 99%
“…One particularly intriguing observation is that the activity of complex (I, II, III, or IV) remained unchanged before and after treatment ( Shults et al, 1995 ). At present, data from the literature show that not only are mitochondrial deficiencies present before drug treatment ( Punzi et al, 2018 ), but also that current drug therapy do not inhibit mitochondrial damage and resolve abnormal mitochondrial functions ( Murthy et al, 2022 ). These findings suggest that targeting the S1P pathway might be therapeutically important for PD patients through regulating mitochondrial function.…”
Section: The Relationship Between S1p and Parkinson’s Diseasementioning
confidence: 99%